A 10-Gb/s inductorless optical receiver in 0.18-μm SiGe BiCMOS. (April 2019) - Xue, Zhe; He, Jin; Fang, Ya; Wang, Hao; Chang, Sheng; Huang, Qijun; Zhu, Yinxia
Abstract: A 10-Gb/s inductorless optical receiver featuring linear characteristic has been designed and implemented using a 0.18-μm SiGe BiCMOS process. As the input stage of the proposed optical receiver, a transimpedance amplifier (TIA) of a common-emitter and common-collector topology with a feedback resistor incorporates DC offset cancellation (DOC) and automatic gain control (AGC) to improve the linearity and broaden the input dynamic range. Followed by a post amplifier and a 50-Ω output buffer, the measured input sensitivity, overload, and dynamic range of the optical receiver are respectively −19.3 dBm, −4 dBm, and 15.3 dB for a bit-error rate of 10 −12  at 10 Gb/s. The whole receiver draws a total current of 24 mA from a 3.3 V supply and the chip has an area of 826 μm × 957 μm.